Mixed problem with nonlocal boundary conditions for a third-order partial differential equation of mixed type. (15th May 2001) - Denche, M.; Marhoune, A. L.
Abstract : We study a mixed problem with integral boundary conditions for a third-order partial differential equation of mixed type. We prove the existence and uniqueness of the solution. The proof is based on two-sided a priori estimates and on the density of the range of the operator generated by the considered problem.